Thematic curriculum design of integrating labor education into kindergarten classes - Hu, Xiao (Pacific International Journal, 2022)
In China, labor education is an important part of the all-round development of the education system and an important part of educational practice activities. The main purpose is to enable students to establish a correct concept of labor, correct their working attitude, love labor and the working people, and develop good working habits. Early childhood education is an important stage in the process of basic education in China. Labor education should be included in its viewing vision and become an important content. It is of great significance to integrate labor education into the theme teaching of large-class children. It can enable children to cultivate good labor literacy, exercise effective practical skills, promote their formation of a sound personality, and promote the development of early childhood education. Through literature research, investigation and interviews, we found that there are some shortcomings in the theme teaching of large classes of children, including that preschool teachers do not pay enough attention to it and do not have a comprehensive understanding; the theme teaching has a single form and the effect is not good;the content tends to be similar, and the evaluation is lagging. In order to effectively solve these problems, preschool teachers should fully focus on the goal of labor education, follow the law of early childhood growth and development, and carry out targeted thematic teaching in combination with children’s daily life. These are also effective strategies for integrating labor education into the theme teaching of large-scale children.